KATA MAHA DALAM TIGA KARYA SASTRA: BUSTAN AL-SALATIN (1640), HIKAYAT RAJA BIKRAMA SAKTI (1830), DAN NEGERI 5 MENARA (2009) - Suswandi, Irwan; Oktavianti, Ikmi Nur; Atmantika, Zanuwar Hakim (Universitas Muhammadiyah Surabaya, 2024)
The use of the word “maha” in the social media era is interesting to discuss. The word “maha”, for some people, is regarding to the divine. This research aims to determine the use and meaning of the word “maha” in three literature manuscripts, namely Bustan al-Salatin (1640), Hikayat Raja Bikrama Sakti (1830) and Negeri 5 Menara (2009). This research is included as qualitative research with a descriptive-analytical design. The data collection method chosen was the note-taking method. The theories used in this research were the collocation theory from Halliday and Hasan (1976) and the meaning component theory from Nida (1975). The data sources for this research were three manuscripts from different periods, namely Bustan al-Salatin (1640), Hikayat Raja Bikrama Sakti (1830), and Negeri 5 Menara (2009). This research involved a corpus approach regarding research data sources. From the results of the analysis, the word “maha” does not only refer to God or divine. In the Bustan al-Salatin manuscript, the word “maha” can refer to God, king, places, activities, animals, and objects; in the Hikayat Raja Bikrama Sakti manuscript, it refers to God and king; and in the Negeri 5 Menara manuscript, it refers to God and objects.